ANALISIS DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN PAI - Ika Kartika; Imas Sa’adiyah; M. Syamsudin Nurflah (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the influence of TikTok social media usage on students' learning interest in Islamic Religious Education (PAI) at SMP PGRI 2 Cidahu Sukabumi. The research addresses the phenomenon of declining student interest in religious lessons amidst the widespread use of digital technology among teenagers. Using a qualitative descriptive approach with triangulation methods, data were collected through participatory observation, in-depth interviews, and documentation studies over six months. Findings indicate that students' interest in PAI learning remains high with 85% active participation, supported by interactive teaching methods and positive teacher-student relationships. TikTok Islamic content contributes significantly to increasing learning interest, with 75% of students accessing religious content and 63% acknowledging its positive influence. However, the platform presents a dual impact: while educational religious content enhances understanding and character building, excessive use causes learning concentration disturbances and time management issues. The study concludes that optimizing PAI learning in the digital era requires balanced integration between conventional approaches and digital media utilization, emphasizing direct worship practices and religious character development through intensive mentoring and digital literacy education.